Exploring Sesquiterpene Lactones from Saussurea lappa: Isolation, Structural Modifications, and Herbicide Bioassay Evaluation - Elson S. Alvarenga; Francisco A. Macías; Stephani S. Ferreira; Juan C. G. Galindo; José M. G. Molinillo (Plants)
Considering the resistance of weeds to different herbicides with different mechanisms of action, the search for new, more selective compounds with low toxicity to other species in nature has been very important for the development of agriculture. Because of that, considering the biological activity of allelochemicals and natural epoxides, four new epoxy compounds derived from dehydrocostus lactone were synthetized and evaluated for their potential herbicide activity against three species of seeds, Allium cepa (onion), Lepidium sativum (garden cress), and Lactuca sativa (lettuce). In assays with A. cepa, compound 4 inhibited radicle length by 80% at 100 μM. Notably, for L. sativum, compound 4 showed significant inhibition, reducing stalk and radicle lengths by 80% at 100 μM, surpassing the performance of the commercial herbicide Logran. However, diol 5 notably inhibited radicle growth by 28% at 100 μM, making the most significant observed effect. One of the noteworthy lactones studied is epoxide 4. This highlights the importance of the epoxide functional group in affecting both radicle and shoot lengths of seeds. Therefore, the synthesis of these compounds has proven advantageous and holds great potential for the development of new herbicides.